Improving Students' Listening Comprehension using YouTube Channel Easy English - Maharani, Eldar Indah; Eusabinus Bunau; Ikhsanudin (Universitas Sarjanawiyata Tamansiswa, 2023)
This research aimed to improve students’ listening comprehension using the YouTube channel Easy English to students at SMA Islam Bawari Pontianak in the tenth grade. The method used in this study was classroom action research, which included planning, acting, observing, and reflecting over two cycles. With 35 students, the study subject was X IIS 4. The data was gathered using observation and measurement techniques. The tools used were an observation checklist, field notes, and a listening comprehension test. The observation checklist was on the students’ performances, class situation, and researcher’s performances. The field note was made based on the students' and researcher’s pre-activity, whilst activity, and post-activity. The listening comprehension test was multiple-choice and consisted of 10 items. The student's listening comprehension improved with each cycle. The students' mean score in the first cycle was 58, which improved to 85 in the second cycle. The result showed that the YouTube Channel Easy English improved students’ listening comprehension in terms of recognizing the primary concept or major gist, identifying supporting information, identifying message moods, and acquiring new vocabulary.